Psalm 26 and Proverbs Tracing wisdom themes - Potgieter, Annette (2014)
The discernment of Psalm 26 as a cultic psalm has prevented noticing vital connections with wisdom literature. These connections with Proverbs and other known wisdom psalms provide clues for the composition of Psalm 26 to be set in the post-exilic period. The way in which wisdom literature is used conveys the religious ethos and daily life of a community. The fact that the wisdom character of Psalm 26 has been overlooked can be viewed as one of the main reasons why Psalm 26 has been interpreted solely in a cultic setting. The sapiential influence of this psalm has been confused to only reflect the cultic aspects. The psalmist wants to live a life according to wisdom as he seeks the rewards of being close to Yahweh.
Keywords: Persian Period; Wisdom influence